2021
DOI: 10.1038/s41467-021-23742-4
|View full text |Cite
|
Sign up to set email alerts
|

Wide-range lifetime-tunable and responsive ultralong organic phosphorescent multi-host/guest system

Abstract: The rational lifetime-tuning strategy of ultralong organic phosphorescence is extraordinarily important but seldom reported. Herein, a series of multi-host/guest ultralong organic phosphorescence materials with dynamic lifetime-tuning properties were reported. By doping a non-room-temperature phosphorescence emitter into various solid host matrices with continuously reduced triplet energy levels, a wide-range lifetime (from 3.9 ms gradually to 376.9 ms) phosphorescence with unchangeable afterglow colors were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(138 citation statements)
references
References 50 publications
2
136
0
Order By: Relevance
“…These mainly include co-crystal assembly, 49 rigid matrix host–guest systems, 83 structurally modified host–guest systems, 84 and dopant-based systems. 54 By dissolving 1,8-naphthalic anhydride in certain organic solid hosts, purely organic phosphorescence with a lifetime of over 600 ms and an overall quantum yield of over 20% were realized, 55 where it was proposed that a cluster exciton spanning the host and guest forms as a transient state before the guest acts as an energy trap for the RTP state. Overall, the key to achieving efficient phosphorescence lies in enhancing k ISC , accelerating phosphorescent decay and minimizing the non-radiative decay rate and quenching rate.…”
Section: Design Of Pure Organic Rtp and Tadf Emittersmentioning
confidence: 99%
See 1 more Smart Citation
“…These mainly include co-crystal assembly, 49 rigid matrix host–guest systems, 83 structurally modified host–guest systems, 84 and dopant-based systems. 54 By dissolving 1,8-naphthalic anhydride in certain organic solid hosts, purely organic phosphorescence with a lifetime of over 600 ms and an overall quantum yield of over 20% were realized, 55 where it was proposed that a cluster exciton spanning the host and guest forms as a transient state before the guest acts as an energy trap for the RTP state. Overall, the key to achieving efficient phosphorescence lies in enhancing k ISC , accelerating phosphorescent decay and minimizing the non-radiative decay rate and quenching rate.…”
Section: Design Of Pure Organic Rtp and Tadf Emittersmentioning
confidence: 99%
“…Accordingly, these two approaches harvest light from both triplet and singlet excitons, allowing the internal quantum efficiency (IQE) of the devices to reach nearly 100%. 45,46 In the last several years, through versatile design principles, such as halogen bonding, 47–49 H-aggregation, 50 and n–π transitions, 51,52 while phosphorescence enhancement strategies based on co-crystallization 49 and rigid matrix host–guest systems, 53–55 pure organic molecules have been progressively endowed with long-lived and strong room-temperature phosphorescence (RTP). Generally, pure organic RTP emitters, including sulfur–nitrogen-containing heteroaromatic derivatives, 56 borate derivatives, 57 polyacid derivatives, 58 etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, introducing a supramolecular host molecule into the AIEgen can effectively enhance the emission efficiency in both the monomer and aggregated states due to the non-covalent interactions between the host and guest molecules ( Liang et al, 2014 ; Song et al, 2014 ; Liang et al, 2016 ; Liow et al, 2017 ). And, doping trace amounts of luminophores into host molecules makes efficient room temperature phosphorescence ( Hirata et al, 2013 ; Kabe and Adachi, 2017 ; Han et al, 2019 ; Lei et al, 2019 ; Lei et al, 2021 ; Xie et al, 2021 ). Therefore, the luminescent properties of organic molecular aggregates are sensitive to molecular packing and intermolecular non-covalent interactions and are highly complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the ultralong RTP in aromatic hydrocarbon materials is extremely rare, ( Clapp, 1939 ; Bilen et al, 1978 ), because of the forbidden intersystem crossing (ISC) process between singlet and triplet excited states. To overcome this issue, the heavy atoms (eg., Br and I) ( Cai et al, 2018 ; Wang et al, 2021b ) and carbonyl groups ( Zhao et al, 2016 ; Jia et al, 2020 ) were incorporated into organic molecules to promote ISC process for achieving ultralong RTP, in combination with the suppression of the nonradiative quenching through rigid environment, ( Wu et al, 2020 ; Zheng et al, 2020 ; Zhou et al, 2020 ; Chen et al, 2021 ; Xie et al, 2021 ), such as crystal engineering and host-guest system. Very recently, Bechtold et al reported that the nonplanar aromatic hydrocarbon, named as 5,6,11,12,17,18-hexahydrobenzo [2,1-p]chrysene (HD), ( Salla et al, 2019 ), can show an ultralong RTP, which was attributed to the pronounced SOC induced by non-planar configuration.…”
Section: Introductionmentioning
confidence: 99%